The Japanese Archipelago sheltered cave lions, not tigers, during the Late Pleistocene - Xin Sun; Lanhui Peng; Takumi Tsutaya; Qigao Jiangzuo; Yoshikazu Hasegawa; Yuxin Hou; Yu Han; Yan Zhuang; Nuno Filipe Gomes Martins; Jazmin Ramos Madrigal; Alberto J. Taurozzi; Meaghan Mackie; et al. (Proceedings of the National Academy of Sciences, 2026)
Lions and tigers, as dominant apex predators, likely became competitors when lions expanded from Africa into Eurasia approximately one million years ago (Ma), forming a lion–tiger transition belt from the Middle East through Central Asia to the Russian Far East. At the easternmost edge of this zone, the Japanese Archipelago has long been considered a Late Pleistocene tiger refugium, supported by large felid subfossils traditionally attributed to tigers ( Panthera tigris ), though their taxonomic identity remained unresolved. To clarify the origin, evolutionary history, and biogeography of Japan’s Pleistocene felids, we analyzed 26 ancient specimens previously assumed to be tigers. Using mitochondrial and nuclear genome hybridization capture and sequencing, paleoproteomics, Bayesian molecular dating, and radiocarbon dating, we found that all ancient Japanese “tiger” remains yielding molecular data were, unexpectedly, cave lions ( Panthera spelaea ). One specimen from Yamaguchi Prefecture, western Japan, was radiocarbon dated to 36,000-34,891 cal. BP. These cave lions likely dispersed to the Japanese Archipelago between ~72.7 and 37.5 thousand years ago (ka), when a land bridge connected northern Japan to the mainland during the Last Glacial Period. Our findings challenge the long-held view that tigers once took refuge in Japan, showing instead that cave lions were widespread in northeast Asia during this period and were the Panthera lineage that colonized Japan, reaching even its southwestern regions despite habitats previously thought to favor tigers.